PLASMA VITAMIN D TRENDS ACROSS VARIOUS AGE GROUPS IN THE COSMOPOLITAN CITY OF PAKISTAN - Umer Saeed1 , Zoolfishan Imran2 , Jamil Ahmed3 , Saman Saeed4 , Faheem Mahmood5 , Mohammad Rizwan6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2023)
ABSTRACT BACKGROUND: Vitamin D belongs to a group of fat-soluble pro-hormones that can be generated from a precursor underneath the skin, 7-dehydrocholesterol, which yields vitamin D3 (cholecalciferol). OBJECTIVES: Measure the plasma vitamin D level trends among various age groups. The study further identified the age group with the highest number of optimum plasma vitamin D levels. METHODOLOGY: Cross-sectional study was completed from June 2020 through August 2022. All samples were obtained from the population of various areas within Lahore, one of the cosmopolitan cities of Pakistan. A 5 ml venous blood from 2661 participants was drawn to measure plasma vitamin D levels. The participants’ age was divided into seven groups and was further stratified into male and female groups. Vitamin D levels were categorized on standard criteria as optimum, mildly deficient, severely deficient, excess, and toxic. The blood samples were analyzed in an ISO-certified laboratory. RESULTS: We enrolled 2661 participants. The highest percentage of vitamin D deficiency was reported in group-3 (21- 30 years; 39.3%). With regards to gender, among males, group one (1-10 years; 24.2%) was found to be most deficient in vitamin D. Further, the optimum plasma levels of vitamin D among females with the highest percentage of vitamin D was in group seven (above 60 years; 25.7%) and group one (1-10 years; 18.9%) among males. CONCLUSION: Our results revealed that the most vulnerable age group with severe vitamin D deficiency was the young age group females (39.3%), and the optimum level was reported in older females (25%), and among males, vitamin D deficiency was detected among older age groups (13.7%) and the optimum level was noticed in younger males. Further studies are required to elucidate the probable causes of severe vitamin D deficiency.